MENINGKATKAN AKTIVITAS BELAJAR IPS KERAGAMAN SUKU BANGSA MELALUI MODEL PEMBELAJARAN BERBASIS PROYEK DI KELAS V SD - Seftinengseh, Nurjihan; Nurul Fauziyah, Vita; Adji Setyorini, Devi; Yudha Aldetya Fanda Febriarta; Priyono Tri Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Conventional teaching methods are often cited as the primary cause of low student engagement and limited understanding of Indonesia's ethnic diversity in elementary education. This study aims to investigate the potential and effectiveness of the Project Based Learning (PjBL) model in enhancing Social Studies (IPS) learning activities for Grade V students. Adopting a library research method, this study analyzes various academic references and previous research findings regarding PjBL implementation in elementary schools. The results indicate that the PjBL model, particularly through the creation of tangible products like the Indonesian Cultural Diversity Map, significantly boosts students' involvement, creativity, and critical thinking. Furthermore, project-based activities allow students to experience cultural pluralism firsthand, fostering a sense of patriotism and mutual respect. Thus, the PjBL model serves as a highly relevant alternative for improving the quality of Social Studies education in elementary schools.